Kiss Me, Cowboy - Palmer, Diana; Palmer, Diana (New York, NY : Zebra Books, Kensington Publishing Corp., 2022)
"New York Times bestselling author Diana Palmer takes reader to Colorado in two novellas where solitary, silent cowboys find their restless hearts tamed by women of uncommon grace and strength"--
Keywords: Ranchers -- Fiction; Cowboys -- Fiction; Man-woman relationships -- Fiction; Weddings -- Fiction; Women screenwriters -- Fiction; Wildlife rehabilitators -- Fiction; Colorado -- Fiction; Romance fiction; Thrillers (Fiction); Western fiction; Novellas